An state-of-the-art design technique in landfill engineering :|a case study - Aykan, S. Birkan. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2001., 2001)
Disposal of solid wastes, the final functional element of the solid waste management system. is a major problem throughout the industrialized world. Sanitary landfilling is today widely recognized as the most common and economic method and viable solution for the disposal of municipal and industrial solid wastes. Despite the implementation of waste reduction recycling and transformation technologies disposal in landfills still remains an important component of integrated solid waste management strategy. The purpose of this study was to present the design steps of sanitary landfills through Sinop (Meşedağı) sanitary landfill project. The study indicates that planning and design of modern landfills involves the application of a variety of scientific. economic and engineering principles. The main criteria in design studies were the Turkish Environmental Regulations. The other main feature of the study was the evaluation of the differeat models and approaches employed in the design of modern landfills. In this manner. it is intended to gather appropriate data by comparing the results. The major topics covered in this study include description of the landfill site, estimation of population and solid waste generation. definition of waste properties, slope and berm stability analysis. design of sub-base liners and Dnal (ap, estimation of leachate generation and design of leachate collection system. design of surface water drainage system, estimation of gas generation and design of gas venting system, design of leachate treatment plant and closure of landfill and longterm monitoring.
Keywords: Sanitary landfills -- Design and construction.; Refuse and refuse disposal.